CFD analysis of effect of area ratio on suddenly expanded flows - Pathan, Khizer Ahmed; Khan, Sher Afghan; Dabeer, P S (IEEE, 2017)
This paper presents the Computational Fluid Dynamic (CFD) analysis to study the effect of area ratio i.e. the ratio of enlarged duct area to nozzle exit area on velocity distribution along axis by varying the nozzle pressure ratios. The convergent-divergent nozzle and suddenly expanded circular duct of larger cross-sectional area are used for analysis. The analysis is done for Mach number 2.0 by varying the area ratios and nozzle pressure ratios. The area ratios for the analysis are 1, 2, 4, 6, 8, 10 and 12. The values of nozzle pressure ratios considered are 2, 4, 6, 8, 10 and 12. The results are compared with the help of graphs and tables. By observing all the results it can be concluded that the flow field in the enlarged duct is strongly influenced by area ratios and Nozzle pressure ratios.